Maternal socioeconomic characteristics and infant mortality from injuries in the Czech Republic 1989-92 - Bobak, M; Pikhart, H; Koupilová, I (Injury prevention, 2000)
OBJECTIVES: Infant and childhood mortality from injuries in Central and Eastern Europe is high but little is known about its determinants. This study examined whether maternal socioeconomic characteristics predict infant mortality from injuries in the Czech Republic. METHODS: Data on all live births registered in the Czech Republic 1989-91 (n=387 496) were linked with the national death register, 1989-92, using the unique national identification number. Effects of maternal socioeconomic characteristics, birth weight and gestational age, recorded in the birth register, on the risk of death from external causes (ICD-9 800-999) were estimated using logistic regression. RESULTS: Of the 195 linked infant deaths from external causes (rate 50/100000 live births), 73% were from suffocation. After controlling for other factors, the risk of death was higher in boys, declined with increasing maternal education (odds ratio for primary v university education 3.5, 95% confidence interval 1.5 to 8.6), maternal age, birth weight and gestational age, and was increased in infants of unmarried mothers and of mothers with higher parity. The effect of education appeared stronger in married mothers and in mothers of low parity. CONCLUSION: The risk of infant death from external causes in this population was strongly associated with maternal and family characteristics.
Keywords: Registries; novorozenec; Infant, Newborn; logistické modely; surveillance populace; Infant; Humans; manželský stav; kojenec; Logistic Models; registrace; kohortové studie; rozložení podle pohlaví; socioekonomické faktory; porodní hmotnost; Predictive Value of Tests; gestační stáří; Female; rizikové faktory; úmrtní listy; kojenecká mortalita; lidé; Death Certificates; Socioeconomic Factors; věk matky; parita; Cohort Studies; Maternal Age; ženské pohlaví; Male; rodné listy; prediktivní hodnota testů; Birth Weight; Parity; rány a poranění; Czech Republic; Infant Mortality; Birth Certificates; Cause of Death; Marital Status; Sex Distribution; Wounds and Injuries; stupeň vzdělání; Population Surveillance; příčina smrti; Česká republika; mužské pohlaví; matky; Educational Status; Gestational Age; Mothers; Risk Factors